TINJAUAN YURIDIS SANKSI ADAT KAILI RAI TERHADAP PELAKU PELECEHAN SEKSUAL: (Studi Kasus di Desa Lende Kecamatan Sirenja) - Moh. Ansar; Suhri Hanafi; Sitti Nurkhaerah; Wahyuni Wahyuni; Taufan B. (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2020)
The problem of how castration sanctions for perpetrators of crimes of sexual violence against children in the perspective of positive law in Indonesia and how Islamic criminal law views castration as a sanction are the focus of the problem in this study. The research method consists of the type of research, data and data sources, data collection techniques and data analysis techniques using a qualitative research approach. Then, as a result of the research, there are differences in Islamic law among scholars regarding the punishment of castration Law Number 17 of 2016 Regarding the stipulation of PERPU Number 1 of 2016 Second Amendment to Law Number 23 Year 2002 Concerning Child Protection Becomes Law against perpetrators of sexual crimes against children, and Islamic law has stipulated penalties for perpetrators of sexual crimes in detail of the facts of their actions, so they cannot (haram) carry out the type of castration punishment in accordance with the argument, namely the hadith of the Prophet Muhammad saw., which prohibits his companions from being castrated.